Polubowne załatwianie spraw w świetle Kodeksu postępowania administracyjnego po nowelizacji z dnia 7 kwietnia 2017 r. - Ziemski, Krystian (Studia Prawa Publicznego, 2018)
This paper discusses the amendments to the code of administrative procedure of 7th April 2017, referring inter alia to the amicable settlement of matters in dispute. The regulation to date concerning conciliation has ceased to be the only method of amicable settlement. An additional method has emerged consisting in mediatory proceedings, which requires a definition of the reciprocal relation between the existing conciliatory proceedings and the mediatory proceedings being introduced. Moreover, this paper analyses the change of the scope of duties of public administration bodies that are about to seek the implementation of arbitrary proceedings. The scope of duties of administration bodies has been considerably extended within this scope. At present, the relevant authorities are obliged to seek to convince the parties that mediatory proceedings are possible and justifiable, this including also the possibility to carry out conciliatory proceedings. Another issue discussed in the paper is the permissible object of mediatory proceedings. Mediatory proceedings may be applied to nearly any type of proceedings. The legislator has not introduced any restrictions in this respect, both as regards the subject or object of the proceedings. Irrespective of the fact whether the proceedings involve parties with conflicting interests or not, an amicable settlement of the dispute is recommended. The introduction of mediatory proceedings should be considered any time, even if there is only one party involved. This is a novelty, compared to the existing possibility of carrying out conciliatory proceedings. No restrictions have been made as regards the object of the proceedings. Consequently mediatory proceedings may be applied to solve the doubts concerning the facts as well as the contents of the applicable legal regulations. This may concern both the disputes regarding the regulations in cases which cannot be solved by the adopted interpretation rules, and in cases where public administration bodies are left with certain freedom of interpretation by the legislator. Also, the nature of the decision to be made in the result of the proceedings may not constitute sufficient grounds for questioning or rejecting the possibility to implement arbitration proceedings. Mediatory proceedings are possible not only in the proceedings ended with acts issued within the discretionary authority or administrative recognition, combined acts, or constitutive or declaratory acts. The only restriction may be the nature of the case contrary to the implementation of amicable proceedings. Also this last question has been thoroughly analysed in this paper.